Expression of genes encoding centrosomal proteins and the humoral response against these proteins in chronic myeloid leukemia - Šmahelová, Jana; Kaštánková, Iva; Poláková, Kateřina Machová; Klamová, Hana; Zemanová, Karla; Tachezy, Ruth; Hamšíková, Eva; Šmahel, Michal (Oncology reports, 2017)
As the extent of centrosome abnormalities in chronic myeloid leukemia (CML) correlates with disease stage and karyotype alterations, abnormal expression of genes encoding centrosomal proteins may be an early prognostic marker of disease progression. In the present study, we showed that in comparison with healthy controls, the expression of four centrosomal genes (AURKA, HMMR, PLK1 and ESPL1) in the peripheral blood of CML patients was significantly enhanced at diagnosis and decreased to the basal level in most patients treated with imatinib mesylate for three months. In the remaining patients (17%), this decrease was delayed and was associated with worse overall survival. The detection of antibodies in sera showed that patients with higher overall antibody production had superior outcomes in terms of achieving major molecular response and failure-free survival. These data suggest that the dynamics of the response of centrosomal genes should be considered as a risk factor and immunity against centrosomal proteins may contribute to treatment response.
Keywords: senioři; regulace genové exprese u leukemie; Cell Cycle Proteins; Male; Female; mladý dospělý; Aged; Middle Aged; Immunity, Humoral; Centrosome; Young Adult; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; centrozom; mužské pohlaví; ženské pohlaví; chronická myeloidní leukemie; Adult; nádorové proteiny; Gene Expression Regulation, Leukemic; proteiny buněčného cyklu; senioři nad 80 let; dospělí; humorální imunita; lidé středního věku; studie případů a kontrol; Aged, 80 and over; lidé; Humans; Neoplasm Proteins; Case-Control Studies